Replication of poliovirus RNA and subgenomic RNA transcripts in transfected cells. - Collis, P S (1992)
Full-length and subgenomic poliovirus RNAs were transcribed in vitro and transfected into HeLa cells to study viral RNA replication in vivo. RNAs with deletion mutations were analyzed for the ability to replicate in either the absence or the presence of helper RNA by using a cotransfection procedure and Northern (RNA) blot analysis. An advantage of this approach was that viral RNA replication and genetic complementation could be characterized without first isolating conditional-lethal mutants. A subgenomic RNA with a large in-frame deletion in the capsid coding region (P1) replicated more efficiently than full-length viral RNA transcripts. In cotransfection experiments, both the full-length and subgenomic RNAs replicated at slightly reduced levels and appeared to interfere with each other's replication. In contrast, a subgenomic RNA with a similarly sized out-of-frame deletion in P1 did not replicate in transfected cells, either alone or in the presence of helper RNA. Similar results were observed with an RNA transcript containing a large in-frame deletion spanning the P1, P2, and P3 coding regions. A mutant RNA with an in-frame deletion in the P1-2A coding sequence was self-replicating but at a significantly reduced level. The replication of this RNA was fully complemented after cotransfection with a helper RNA that provided 2A in trans. A P1-2A-2B in-frame deletion, however, totally blocked RNA replication and was not complemented. Control experiments showed that all of the expected viral proteins were both synthesized and processed when the RNA transcripts were translated in vitro. Thus, our results indicated that 2A was a trans-acting protein and that 2B and perhaps other viral proteins were cis acting during poliovirus RNA replication in vivo. Our data support a model for poliovirus RNA replication which directly links the translation of a molecule of plus-strand RNA with the formation of a replication complex for minus-strand RNA synthesis.